Addressing Domestic Violence in Iraqi Family Law: A Critical Analysis and Recommendations - Dakhil, Yousra Sabri (Universitas Muhammadiyah Sidoarjo, 2023)
This study delves into the complex interplay between domestic violence and the institution of marriage within the framework of Iraqi family law, focusing on the rights of wives to seek separation in cases of abuse. The research employs a legal analysis approach to scrutinize the existing legal texts, judicial applications, and their impact on marital relationships. Findings reveal a disconnect between the legislation and its practical application, with judicial discretion often prioritizing family preservation over the well-being of the wife. The study highlights the need for legal reform to explicitly grant wives the right to seek separation in cases of any form of domestic violence and advocates for the criminalization of domestic violence. Furthermore, it underscores the importance of conducting seminars and conferences to comprehensively address domestic violence as a societal issue and calls for increased research efforts in this domain. This research offers a critical examination of the status quo and proposes tangible steps towards safeguarding the rights and well-being of spouses affected by domestic violence within the Iraqi legal context. Highlights : The study reveals a disconnection between Iraqi family law and the practical application of rights for abused wives, emphasizing the need for legal reform. Advocacy for explicit legal provisions granting wives the right to seek separation in cases of domestic violence. Emphasizing the importance of addressing domestic violence through seminars, conferences, and increased research efforts to protect the well-being of spouses. Keywords : Domestic Violence, Iraqi Family Law, Marital Separation, Legal Reform, Judicial Discretion